Because I am a girl the state of the world's girls 2014 pathways to power : creating sustainable change for adolescent girls - Gaag, Nikki van der (Plan, 2014)
This is the eighth report in Plan International’s annual State of the World’s Girls series, Pathways to Power: Creating Sustainable Change for Adolescent Girls. It asks: what will shift the unequal power relations that bolster gender discrimination, injustice and inequality for girls and women in some form in every country in the world? How does power operate and govern and how can it be reconstructed so that equality for girls exists? Girls’ participation as a form of collective power to change the status quo is explored. The report is available in a variety of accessible formats and languages. A youth summary is suitable for youth and adolescents while an executive summary provides highlights for general consumption. The full report includes all details and research that was conducted to perform the study.